USE OF THE ADSORPTION CATALYTIC METHOD FOR PURIFICATION OF EMISSION OF FORMING SITES OF FOUNDRY SHOPS OF VAPORS OF PHENOL AND FORMALDEHYDE - A. S. Panasyugin; V. A. Lomonosov; O. L. Smorygo (Литьë и металлургия, 2014)
The purpose of this article is studying of process of neutralization of the phenol and formaldehyde vapor by adsorption and catalytic method.